Crude Oil Price Volatility and the Nigerian Economy - Mgbomene, Chukunalu; Ashakah, Felix Onoriode; Metieh, Felix Chukwuka; Okoro, Esther Nkechi; Dim, Henry Chinedu; Opara, Festus Ndidi (International Journal of Energy Economics and Policy, 2025)
This research analyzed crude oil price volatility and the Nigerian economy for the period 1990:Q1-2023:Q4. The independent variables were crude oil price, exchange rate and oil revenue while the dependent variables were GDP, government revenue, foreign exchange reserve and income level (per capita income). Four models were formulated. Data were analyzed using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH). The results revealed strong evidence of volatility clustering in crude oil prices; the availability of new crude oil prices increased conditional volatility by a high magnitude. There was a significant negative effect of crude oil price volatility on the growth of the Nigerian economy while crude oil price volatility increased Nigeria’s foreign reserve, government revenue and income level. In addition, the exchange rate and oil revenue significantly increased the crude oil price volatility – an economic growth nexus in Nigeria. The study concluded that crude oil price hurts the Nigerian economy. However, crude oil price volatility exerted a positive effect on government revenue, foreign exchange reserve and income level in Nigeria during the period of the study. It was recommended that the government should devise a strategy to deviate the economy away from oil dependency to make the economy less vulnerable to oil price shocks.